Boron nitride-aramid composite coaxial fiber and preparation method thereof

Through coaxial spinning technology and thermal drawing drying process, boron nitride nanosheets are induced to achieve high content and high axial orientation in boron nitride-aramid composite coaxial fibers, solving the problem of poor thermal conductivity in boron nitride fibers and achieving high-strength and high-thermal conductivity coaxial fibers.

CN116288802BActive Publication Date: 2025-03-14TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310370476.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-03-14
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

The boron nitride nanosheet content in existing boron nitride fibers is low, easy to produce space voids, and low axial orientation, resulting in poor thermal conductivity.

Method used

Coaxial spinning technology is used to use the aramid nanofiber solution as the core layer spinning liquid, and the boron nitride nanosheet-aramid nanofiber mixed solution as the shell spinning liquid. The outer shell boron nitride nanosheets are induced to rotate and axially oriented through the heat-pulling drying process.

Benefits of technology

The boron nitride coaxial fibers are achieved to simultaneously improve mechanical and thermal conductivity under high content, and overcome the problems of low content of boron nitride nanosheets and low axial orientation in traditional uniaxial fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116288802B_ABST
    Figure CN116288802B_ABST
Patent Text Reader

Abstract

The present application provides a boron nitride-aramid composite coaxial fiber and a preparation method thereof, the preparation method comprising the following steps: S1: preparing an aramid nanofiber solution as a core layer spinning solution, and preparing a boron nitride nanosheet-aramid nanofiber mixed solution as a shell layer spinning solution; wherein the mass fraction of the boron nitride nanosheet in the boron nitride nanosheet-aramid nanofiber mixed solution is 40wt% to 90wt%; S2: coaxially spinning the core layer spinning solution and the shell layer spinning solution to obtain a gel-state coaxial fiber precursor; S3: washing the gel-state coaxial fiber precursor, drying while stretching, i.e. obtaining a boron nitride-aramid composite coaxial fiber. The preparation method selects specific core layer spinning solution and shell layer spinning solution, and adopts coaxial spinning technology combined with stretching and drying process, so that the prepared boron nitride-aramid composite coaxial fiber exhibits excellent comprehensive thermal conductivity and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite fibers, and in particular to a boron nitride-aramid composite coaxial fiber and a preparation method thereof. Background Art

[0002] Two-dimensional boron nitride nanosheets have a layered hexagonal structure similar to graphene. The theoretical value of the in-plane thermal conductivity of a single-layer nanosheet can be as high as 2000W / mK, but the boron nitride fibers reported so far are usually composite uniaxial fibers with a loading of less than 50wt%, resulting in the thermal conductivity of the resulting composite fibers being generally less than 6W / mK. In addition, existing boron nitride nanosheets are usually peeled off from hexagonal boron nitride powders with an AB-type stacked structure. Because of the presence of polar boron-nitrogen bonds and the partial polarization of electron pairs, the interaction between boron nitride layers is relatively strong, making it difficult to peel off. Boron nitride nanosheets with insufficient peeling have a small diameter-to-thickness ratio, large in-plane stiffness, and extremely poor fiber self-assembly, which leads to the easy generation of space gaps during the uniaxial fiber assembly and stacking process, especially in the fiber center area, which in turn affects the axial orientation of the boron nitride nanosheets and the mechanical and thermal conductivity properties of the final fiber. Although the composite of boron nitride nanosheets and high molecular polymers can avoid space gaps and improve the mechanical strength of the fiber to a certain extent, the introduction of high molecular polymers as thermal resistance will inhibit heat transfer between boron nitride nanosheets, making it impossible to fully utilize the high thermal conductivity of boron nitride nanosheets, thereby sacrificing the overall thermal conductivity of the composite fiber. Summary of the invention

[0003] In order to address the deficiencies in the prior art, the purpose of the present application is to provide a method for preparing boron nitride-aramid composite coaxial fibers, by using aramid nanofiber solution as the core layer spinning solution and a boron nanosheet-aramid nanofiber mixed solution as the shell layer spinning solution for coaxial spinning and combined with hot drawing and drying, the coaxial interface shear deformation induces the outer shell layer boron nitride nanosheets to rotate and axially orientate, which can solve the problems of low boron nitride nanosheet content, easy generation of space gaps, and low axial orientation in traditional boron nitride uniaxial fibers, thereby achieving the goal of simultaneously improving the mechanical and thermal conductivity properties of boron nitride coaxial fibers at a high content.

[0004] In addition, the present application also provides a boron nitride-aramid composite coaxial fiber prepared by the above preparation method.

[0005] To achieve the above object, the present application provides a method for preparing a boron nitride-aramid composite coaxial fiber, comprising the following steps:

[0006] S1: preparing an aramid nanofiber solution as a core layer spinning solution, and preparing a boron nitride nanosheet-aramid nanofiber mixed solution as a shell layer spinning solution; wherein the mass fraction of the boron nitride nanosheet in the boron nitride nanosheet-aramid nanofiber mixed solution is 40wt% to 90wt%;

[0007] S2: coaxially spinning the core layer spinning solution and the shell layer spinning solution, and then washing to obtain a gel-state coaxial fiber precursor;

[0008] S3: thermally drawing and drying the gel-state coaxial fiber precursor to obtain boron nitride-aramid composite coaxial fiber.

[0009] In some possible implementations, step S1 includes:

[0010] Step S11: adding aramid chopped fiber yarn into a super acid solvent and subjecting it to high-speed shear emulsification to obtain the aramid nanofiber solution;

[0011] Step S12: adding the boron nitride nanosheets into a super acid solvent and performing a first high-speed shear emulsification to achieve effective exfoliation, and performing a second high-speed shear emulsification to mix the effectively exfoliated boron nitride nanosheets and aramid nanofibers to obtain the boron nitride nanosheet-aramid nanofiber mixed solution;

[0012] Wherein, the super acid solvent is at least one of trifluoromethanesulfonic acid, chlorosulfonic acid or methanesulfonic acid.

[0013] In some possible implementations, the shear speed of the high-speed shear emulsification in step S11 is 6000-20000 rpm, and the shear time is 2-20 min;

[0014] The shearing speed of the first high-speed shear emulsification in step S12 is 6000-20000 rpm, and the shearing time is 1-3 hours. The shearing speed of the second high-speed shear emulsification is 6000-20000 rpm, and the shearing time is 2-20 minutes.

[0015] In some possible implementations, the thickness of the effectively exfoliated boron nitride nanosheets is less than 10 nm, and the average sheet diameter is 500 nm to 2 μm.

[0016] In some possible implementations, the concentration of the aramid nanofiber solution is 10 to 100 mg / mL;

[0017] The concentration of the boron nitride nanosheet-aramid nanofiber mixed solution is 20-200 mg / mL.

[0018] In some possible implementations, the step of "hot-draw drying" includes stretching the gel-state coaxial fiber precursor while drying it; the elongation of the stretching is 4% to 20%, the drying temperature is 60 to 200° C., and the drying time is 10 to 60 minutes.

[0019] In some possible implementations, step S2 specifically includes the following steps:

[0020] The boron nitride nanosheet-aramid nanofiber mixed solution is connected to the outer channel of the coaxial needle, and the aramid nanofiber solution is connected to the inner channel of the coaxial needle. The fibers are extruded through the coaxial needle, and the extruded fibers are drawn and refined while passing through the coagulation liquid to obtain the gel-state boron nitride coaxial fiber precursor.

[0021] In some possible implementations, the extrusion spinning rate of the inner channel is 0.05 to 0.5 mL / min, and the extrusion spinning rate of the outer channel is 0.1 to 1 mL / min; the extrusion spinning rate ratio of the inner channel to the outer channel is 1:4 to 4:1;

[0022] The coagulation liquid is at least one of deionized water, ethanol or isopropanol; the line speed of the wire drawing process is 3 to 30 cm / s.

[0023] The present application also provides a boron nitride-aramid composite coaxial fiber prepared by the above preparation method, wherein the boron nitride-aramid composite coaxial fiber comprises an outer shell layer composed of a boron nitride nanosheet-aramid nanofiber composite material, and a core layer composed of aramid nanofibers.

[0024] In some possible embodiments, the diameter of the boron nitride-aramid composite coaxial fiber is 60 to 200 μm, the thickness of the outer shell layer is 20 to 50 μm, and the diameter of the core layer is 20 to 100 μm; the ratio of the diameter of the boron nitride-aramid composite coaxial fiber to the diameter of the core layer is 3:1 to 1:3.

[0025] The preparation method of the boron nitride-aramid composite coaxial fiber provided in the present application uses aramid nanofiber solution as the core layer spinning solution, and uses a boron nitride nanosheet-aramid nanofiber mixed solution as the shell layer spinning solution, and adopts coaxial spinning technology combined with a stretching and drying process, so that the high thermal conductivity boron nitride shell and the high-strength aramid core are effectively separated to maintain their respective performance advantages, and at the same time, the synergistic effect gives the obtained coaxial fiber high strength and high thermal conductivity. In addition, due to the mismatch of mechanical properties between the inner and outer layers of the coaxial fiber, shear stress will be generated at the inner and outer interfaces during the stretching and drying process, thereby inducing the outer shell layer boron nitride nanosheets to rotate and axially oriented, and the aramid nanofiber core as the main mechanical support can effectively improve the axial orientation and close-packed stacking of the outer shell layer boron nitride nanosheets, thereby further improving the thermal conductivity of the coaxial fiber. This preparation method can effectively solve the problems of low boron nitride nanosheet content, easy generation of space gaps, and low axial orientation that are difficult to overcome in traditional uniaxial fibers, and achieve the goal of simultaneously improving mechanical and thermal conductivity of boron nitride coaxial fibers at high content. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the cross-sectional structure of the boron nitride-aramid composite coaxial fiber in this application.

[0027] Figure 2 Schematic diagram of the process for preparing the boron nitride-aramid composite coaxial fiber in Examples 1 to 3.

[0028] Figure 3 This is a scanning electron microscope image of the cross section of the boron nitride-aramid composite coaxial fiber in Example 1.

[0029] Figure 4 This is a scanning electron microscope image of the cross section of the aramid-boron nitride composite uniaxial fiber in Comparative Example 1.

[0030] Figure 5 This is a scanning electron microscope image of the cross section of the aramid-boron nitride composite hollow fiber in Comparative Example 2.

[0031] Main component symbols

[0032] Boron nitride-aramid composite coaxial fiber 100

[0033] Shell layer 10

[0034] Core layer 20

[0035] Shear stress F DETAILED DESCRIPTION

[0036] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0037] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0038] The present application provides a method for preparing a boron nitride-aramid composite coaxial fiber, comprising the following steps:

[0039] S1: preparing an aramid nanofiber solution as a core layer spinning solution, and preparing a boron nitride nanosheet-aramid nanofiber mixed solution as a shell layer spinning solution; wherein the mass fraction of the boron nitride nanosheet in the boron nitride nanosheet-aramid nanofiber mixed solution is 40wt% to 90wt%;

[0040] S2: coaxially spinning the core layer spinning solution and the shell layer spinning solution, and then washing to obtain a gel-state coaxial fiber precursor;

[0041] S3: thermally drawing and drying the gel-state coaxial fiber precursor to obtain boron nitride-aramid composite coaxial fiber.

[0042] The present application starts from the perspective of the coaxial structural distribution of boron nitride nanosheets in the fiber matrix, uses aramid nanofiber solution as the core layer spinning solution to form the core layer, and uses a high-content boron nitride nanosheet-aramid nanofiber mixed solution as the shell layer spinning solution to form the outer shell layer. The high thermal conductivity boron nitride outer shell and the high-strength aramid core are effectively separated to maintain their respective performance advantages, while synergistically giving the resulting coaxial fiber high strength and high thermal conductivity.

[0043] Figure 1 This is a schematic diagram of the cross-sectional structure of the boron nitride-aramid composite coaxial fiber 100 in this application. The core layer 20 of the aramid nanofiber as the main mechanical support can effectively improve the axial orientation and close-packed stacking of the boron nitride nanosheets in the outer shell layer 10. The core lies in the mismatch of mechanical properties between the inner and outer layers of the coaxial fiber. During the synchronous stretching and drying process, shear stress F will be generated at the inner and outer interfaces, thereby inducing the boron nitride nanosheets in the outer shell layer 10 to rotate and axially orient. This preparation method can effectively overcome the problems of low boron nitride nanosheet content, easy generation of space gaps, and low axial orientation that are difficult to overcome in traditional boron nitride uniaxial fibers, and achieve the goal of simultaneously improving the mechanical and thermal conductivity of boron nitride coaxial fibers at high content. In addition, the process is simple, easy to control, and is expected to achieve industrial production.

[0044] In some embodiments, step S1 specifically includes:

[0045] Step S11: adding aramid chopped fiber yarn into a super acid solvent to dissolve and disperse the aramid nanofiber solution by high-speed shear emulsification, wherein the shear emulsification speed of the high-speed shear emulsification is 6000-20000 rpm, the shearing time is 2-20 min, and the concentration of the prepared aramid nanofiber solution is 10-100 mg / mL;

[0046] Step S12: Add the boron nitride nanosheets to the super acid solvent for the first high-speed shear emulsification to achieve effective exfoliation, and mix the effectively exfoliated boron nitride nanosheets with aramid nanofibers for the second high-speed shear emulsification to obtain the boron nitride nanosheet-aramid nanofiber mixed solution; the shear speed of the first high-speed shear emulsification is 6000-20000 rpm, the shear time is 1-3 hours, and the shear speed of the second high-speed shear emulsification is 6000-20000 rpm, and the shear time is 2-20 minutes. The concentration of the boron nitride nanosheet-aramid nanofiber mixed solution is 20-200 mg / mL.

[0047] Wherein, the super acid solvent is at least one of trifluoromethanesulfonic acid, chlorosulfonic acid or methanesulfonic acid. Preferably, the super acid solvent is trifluoromethanesulfonic acid which has a more stable chemical property.

[0048] In the dispersion process of aramid chopped fiber yarn, the faster the shear speed of high-speed shear emulsification, the faster the dissolution rate of aramid chopped fiber yarn. The higher the concentration of aramid nanofiber spinning solution, the greater its viscosity, and the larger the hole diameter of the coaxial needle required for spinning. The specific parameter setting can be adjusted according to demand.

[0049] In this application, high-speed shear emulsification is combined with superacid solvent to effectively exfoliate boron nitride nanosheets. The boron nitride raw material is hexagonal boron nitride powder, and the original average sheet diameter is 5 to 15 μm. The thickness of the boron nitride nanosheet after effective exfoliation is less than 10 nm, and the average sheet diameter is 500 nm to 2 μm. Among them, the greater the high-speed shear emulsification rate, the shorter the time required for effective exfoliation of the boron nitride nanosheet. The greater the shear speed of the mixing of boron nitride nanosheets and aramid nanofibers, the shorter the time required for sufficient mixing. The greater the concentration of the boron nitride nanosheet-aramid nanofiber mixed solution, the greater its viscosity, and the larger the hole diameter of the coaxial needle required for spinning. The specific parameter settings can be adjusted according to demand.

[0050] The washing process in step S2 is to remove the residual super acid solvent in the gel-state boron nitride fiber precursor.

[0051] In some embodiments, step S2 specifically includes the following steps:

[0052] The boron nitride nanosheet-aramid nanofiber mixed solution is connected to the outer channel of the coaxial needle, and the aramid nanofiber solution is connected to the inner channel of the coaxial needle, extruded through the coaxial needle, and drawn and pulled to refine the fibers while coagulating in the coagulation liquid to obtain the gel-state boron nitride coaxial fiber precursor.

[0053] The extrusion spinning rate of the inner channel is 0.05-0.5 mL / min, the extrusion spinning rate of the outer channel is 0.1-1 mL / min, and the extrusion spinning rate ratio of the inner channel to the outer channel is 1:4-4:1. The specific extrusion spinning rate parameter setting can be adjusted according to the coaxial needle model used, the viscosity of the spinning solution, the overall diameter of the target coaxial fiber and the ratio of the inner and outer diameters, etc. During the spinning process, the coaxial needle outlet needs to be completely immersed in the coagulation liquid at all times.

[0054] Preferably, the coagulation liquid is a polar small molecule solvent that is easy to remove, and the small molecule has a hydroxyl group, such as deionized water, ethanol, isopropanol, etc. The polar small molecule solvent has the ability to quickly capture the hydrogen protons of the superacid in the spinning solution, and in this process can quickly enter the spinning solution to produce hydrogen bond interactions with the aramid nanofibers, and the macroscopic overall performance is that the spinning solution extruded through the coaxial needle produces coagulation and fiberization. In addition, the easy removal property allows the subsequent drying process to be carried out quickly, thereby achieving rapid mass production of fibers.

[0055] The drawing and pulling process of thinning the fibers is carried out while the fibers are coagulated by the coaxial needle extrusion, and the required drawing and pulling line speed is 3 to 30 cm / s. The greater the viscosity of the spinning solution, the greater the maximum drawing and pulling line speed that can be achieved. The greater the drawing and pulling line speed, the thinner the coaxial fiber precursor obtained and the smaller the diameter. The specific drawing and pulling line speed can be adjusted according to the viscosity of the spinning solution and the model of the coaxial needle.

[0056] The "hot-drawing drying" in step S3 is to stretch the obtained gel-state boron nitride fiber precursor to a certain elongation and dry it in an oven at the same time.

[0057] In some embodiments, the stretching elongation is 4% to 20%, the drying temperature is 60 to 200° C., and the drying time is 10 to 60 min.

[0058] During the simultaneous stretching and drying process, the boron nitride nanosheets in the outer shell of the composite coaxial fiber will be axially oriented and densified under the shear force induced by the internal and external interfaces of the composite coaxial fiber. The greater the elongation of the stretching, the higher the orientation degree of the boron nitride nanosheets of the obtained coaxial fiber, the denser the fiber, and the smaller the diameter. The higher the drying temperature, the shorter the required drying time, the denser the obtained coaxial fiber, and the smaller the diameter. The specific stretching elongation and drying temperature can be adjusted according to demand.

[0059] The present application also provides a boron nitride-aramid composite coaxial fiber prepared by the above-mentioned preparation method, wherein the boron nitride-aramid composite coaxial fiber comprises an outer shell layer composed of a boron nitride nanosheet-aramid nanofiber composite material and a core layer composed of aramid nanofibers. The boron nitride-aramid composite coaxial fiber comprises an outer shell layer of a high thermal conductivity path composed of high-content boron nitride nanosheets with high orientation and close arrangement and a main mechanical support core layer composed of densified aramid nanofibers, which well takes into account both the mechanical properties and thermal conductivity of the boron nitride fiber.

[0060] The diameter of the boron nitride-aramid composite coaxial fiber is 60-200 μm, the thickness of the outer shell is 20-50 μm, the diameter of the core layer is 20-100 μm, and the ratio of the diameter of the boron nitride-aramid composite coaxial fiber to the diameter of the core layer is 3:1-1:3. The overall diameter and the inner and outer diameter thickness ratio of the coaxial fiber can be controlled by parameters such as the viscosity of the spinning solution, the needle model, the spinning and drawing speed, the hot drawing elongation, and the ratio of the inner and outer channel spinning speeds.

[0061] The scheme in the present application will be explained below in conjunction with specific embodiments and comparative examples. Those skilled in the art will understand that the following examples are only used to explain the present invention and cannot be understood as limiting the present invention. The main raw materials and equipment used in the specific embodiments and comparative examples are conventional commercial products or open source. The aramid fiber yarn raw material is commercially available aramid short-cut ultrafine fiber yarn, and the boron nitride nanosheet raw material is hexagonal boron nitride powder, and the original average sheet diameter is 5 to 15 μm. The coaxial needle is a commercially available stainless steel coaxial needle, and the model is 15G to 22G (outer diameter) / 20G to 32G (inner diameter).

[0062] Example 1

[0063] Please refer to Figure 2 This embodiment provides a method for preparing a boron nitride-aramid composite coaxial fiber, comprising the following steps:

[0064] (1) Preparation of aramid nanofiber solution

[0065] 6 g of completely dried aramid short-cut ultrafine fibers were gradually added into 120 mL of trifluoromethanesulfonic acid solvent and operated at a high-speed shear emulsification speed of 8000 rpm for 20 min to achieve effective dissolution and dispersion of the aramid short-cut fiber yarn. After standing for 8 h to remove bubbles, an aramid nanofiber solution with a concentration of 50 mg / mL that can be directly used for spinning was obtained.

[0066] (2) Preparation of Boron Nitride Nanosheet-Aramid Nanofiber Mixed Solution

[0067] 3g of completely dried hexagonal boron nitride powder was added to 60mL of trifluoromethanesulfonic acid and dispersed for 2h under high-speed shear emulsification at a speed of 8000rmp to obtain effectively exfoliated boron nitride nanosheets. Subsequently, 60mL of aramid nanofiber solution with a concentration of 50mg / mL was added, and high-speed shear emulsification was performed at a speed of 8000rmp for 15min. Finally, after standing for 8h to remove bubbles, a boron nitride nanosheet-aramid nanofiber mixed solution with a concentration of 50mg / mL was obtained, in which the mass fraction of boron nitride nanosheets was 50wt%.

[0068] (3) Coaxial spinning

[0069] A stainless steel coaxial needle of model 17G (diameter of the outer channel 1110μm) / 22G (diameter of the inner channel 420μm) was selected for coaxial spinning. The outer channel of the coaxial needle was connected to the above-mentioned boron nitride nanosheet-aramid nanofiber mixed solution as the shell spinning solution, and the inner channel was connected to the above-mentioned aramid nanofiber solution as the core spinning solution. The extrusion spinning rate of the inner channel was 0.2mL / min, and the extrusion spinning rate of the outer channel was 0.4mL / min. During the coaxial spinning process, the outlet of the coaxial needle was completely immersed in the deionized water coagulation tank, and the coaxial fiber extruded by the coaxial needle was thinned and coagulated at the same time by roller drawing at a linear speed of 20cm / s to obtain a gel coaxial fiber precursor. The obtained gel boron nitride coaxial fiber precursor was further washed in deionized water in a cleaning tank to remove the residual trifluoromethanesulfonic acid.

[0070] (4) Hot-drawing drying

[0071] The washed gel-state boron nitride coaxial fiber precursor is stretched to an elongation of 12% and dried in an oven at 80°C for 30 minutes, and then collected to obtain a boron nitride-aramid composite coaxial fiber with an outer shell layer containing 50 wt% boron nitride.

[0072] The cross-sectional scanning electron microscope image of the boron nitride-aramid composite coaxial fiber prepared in Example 1 is as follows: Figure 3 As shown, it can be seen that the composite fiber material has an obvious coaxial structure, the overall fiber diameter is about 120μm, the core layer is a dense core composed of pure aramid nanofibers, with a diameter of about 40μm, and the outer shell is composed of high-content boron nitride nanosheets with high axial orientation and close stacking, with a thickness of about 40μm. The overall diameter-thickness ratio of the inner and outer layers of the coaxial fiber is about 1:2. The stacking patterns of the boron nitride nanosheets in the outer shell are highly zigzag-shaped and distributed around the surface of the core layer of the aramid nanofiber, and the whole looks like a tree-shaped growth ring wrapped around the core layer.

[0073] Comparative Example 1

[0074] The difference between Comparative Example 1 and Example 1 is that in step (3), a stainless steel uniaxial needle of model 17G (the diameter of the uniaxial channel is 1110 μm) is used to directly perform uniaxial spinning on a 50 wt% boron nitride nanosheet-aramid nanofiber mixed solution, and the extrusion spinning rate is 0.4 mL / min.

[0075] The cross-sectional scanning electron microscope image of the aramid / boron nitride composite uniaxial fiber prepared in Comparative Example 1 is as follows: Figure 4 As shown. It can be seen that the overall diameter of the aramid / boron nitride composite uniaxial fiber is about 120μm, and the fiber only produces a certain degree of axial orientation and close-packed stacking patterns of boron nitride nanosheets at a surface depth of about 10μm, while the boron nitride nanosheets appear disordered and porous in most areas in the middle of the fiber. This is because the boron nitride uniaxial fiber does not have an inner and outer layer interface similar to the coaxial fiber in Example 1. When it undergoes the same hot drawing process, it cannot produce interfacial shear-induced orientation of the boron nitride nanosheets. It is only the drying process from the outside to the inside that produces close packing and orientation at a certain surface depth. Therefore, combined with the analysis of Example 1 and Comparative Example 1, it can be concluded that the inner aramid nanofiber core of the coaxial fiber makes a great contribution to the axial orientation of the boron nitride nanosheets in the outer shell.

[0076] Comparative Example 2

[0077] The difference between Comparative Example 2 and Example 1 is that in step (3), the inner channel of the coaxial needle is connected to deionized water.

[0078] In Comparative Example 2, the inner channel of the coaxial needle is changed from aramid nanofiber liquid to deionized water to prepare an aramid / boron nitride composite hollow fiber material. The cross-sectional scanning electron microscope image of the aramid / boron nitride composite hollow fiber prepared in Comparative Example 2 is shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the hollow fiber nanocomposite material with 50wt% boron nitride content in the outer shell layer obtained in Comparative Example 2 is similar to the outer shell layer of the coaxial fiber in Example 1, except that the fiber obtained in Comparative Example 2 has no aramid nanofiber core and exhibits a hollow structure. Since there is no induction mechanism for the inner aramid core of the coaxial fiber to orient the boron nitride in the outer shell layer, and the boron nitride nanosheets have a relatively large degree of freedom under the hollow structure, the boron nitride nanosheets of the hollow fiber obtained in Comparative Example 2 are disordered as a whole and have a very low degree of orientation.

[0079] In order to verify the performance advantages of the boron nitride-aramid composite coaxial fiber obtained by the coaxial spinning preparation method of the present application, the composite fiber materials prepared in Example 1 and Comparative Examples 1-2 were tested for performance, and the orientation factor (measured by wide-angle X-ray diffraction), density, mechanical strength and thermal conductivity of the coaxial fiber of Example 1, the uniaxial fiber of Comparative Example 1 and the hollow fiber of Comparative Example 2 were measured and analyzed and compared. The performance test results of Example 1 and Comparative Example 1 are shown in Table 1.

[0080] Table 1 Performance comparison between Example 1 and Comparative Examples 1-2

[0081]

[0082] As can be seen from Table 1, compared with the uniaxial fiber in Comparative Example 1, the coaxial fiber in Example 1 exhibits better orientation, density, mechanical strength and thermal conductivity as a whole. Among them, the high orientation of the coaxial fiber is consistent with the outer shell composed of highly oriented and closely packed boron nitride nanosheets shown in the scanning electron microscope photograph, thereby forming a high thermal conductivity outer shell passage, so that the thermal conductivity of the coaxial fiber is as high as 13.5W / (m·K), which is nearly 120% higher than the uniaxial boron nitride fiber in Comparative Example 1. Correspondingly, the high-strength aramid nanofiber core gives the coaxial fiber high-strength mechanical properties, with a tensile strength of up to 277.9KPa, which is nearly 100% higher than the uniaxial fiber; the Young's modulus is 13.6GP, which is also nearly 50% higher. Furthermore, due to the lack of mechanical support of the aramid core and the orientation induction effect of boron nitride, the overall performance of the boron nitride hollow fiber obtained in Comparative Example 2 is greatly reduced. In general, the obtained high-strength and high-thermal conductivity coaxial fiber composite material includes a high-thermal conductivity path outer shell layer composed of highly oriented and closely packed high-content boron nitride nanosheets and a main mechanical support core layer composed of densified aramid nanofibers. The coaxial fiber takes into account both the mechanical properties and thermal conductivity of boron nitride fibers.

[0083] In addition, the induction mechanism of the orientation of the boron nitride outer shell layer by the core of the aramid nanofiber in the inner layer of the coaxial fiber in the present invention is fully confirmed and ubiquitous, even under the condition that the coaxial fiber has different boron nitride outer shell content and inner and outer layer diameter ratio. In practical applications, the relevant properties of the boron nitride coaxial fiber finally obtained can be regulated and optimized to a certain extent by appropriately adjusting the specific parameters of each step of coaxial spinning. For example, by appropriately increasing the content of boron nitride nanosheets in the outer shell of the coaxial fiber to further improve the thermal conductivity of the fiber or increasing the thickness ratio of the inner and outer layers to further improve the mechanical properties of the fiber, the boron nitride nanosheets in the outer shell of the coaxial fiber can maintain a high degree of axial orientation and tight stacking. Other embodiments of the present invention are further described below through some examples.

[0084] Example 2

[0085] The difference between Example 2 and Example 1 is that in step (2), 25.7 mL of 50 mg / mL aramid nanofiber solution is added to the effectively stripped boron nitride nanosheets, so that the mass fraction of boron nitride nanosheets in the boron nitride nanosheet-aramid nanofiber mixed solution is 70 wt%.

[0086] Compared with Example 1, the content of boron nitride nanosheets in the shell spinning solution is increased to 70wt% in Example 2, and finally a boron nitride-aramid composite coaxial fiber with a boron nitride nanosheet content of 70wt% in the outer shell layer is obtained. The thermal conductivity of the boron nitride-aramid composite coaxial fiber can be as high as 17.3W / (m·K), and the tensile strength can still be maintained at 172MPa.

[0087] Example 3

[0088] The difference between Example 3 and Example 1 is that the extrusion spinning rate of the inner channel in step (3) is 0.4 mL / min.

[0089] Compared with Example 1, Example 3 improves the extrusion spinning rate of the inner channel, so that the inner and outer diameter thickness ratio of the final coaxial fiber is close to 1:1. The tensile strength of the fiber can be as high as 340 MPa, while the thermal conductivity can still be maintained at 11.3 W / (m·K).

[0090] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the above preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a boron nitride-aramid composite coaxial fiber, characterized in that: The following steps are involved: S1: preparing an aramid nanofiber solution as a core layer spinning solution, and preparing a boron nitride nanosheet-aramid nanofiber mixed solution as a shell layer spinning solution; wherein the mass fraction of the boron nitride nanosheet in the boron nitride nanosheet-aramid nanofiber mixed solution is 40wt% to 90wt%; S2: coaxially spinning the core layer spinning solution and the shell layer spinning solution, and then washing to obtain a gel-state coaxial fiber precursor; S3: drying the gel-state coaxial fiber precursor and stretching it at the same time, wherein the elongation of the stretching is 4% to 20%, thereby obtaining a boron nitride-aramid composite coaxial fiber.

2. The preparation method according to claim 1, characterized in that Step S1 includes: Step S11: adding aramid chopped fiber yarn into a solvent and subjecting it to high-speed shear emulsification to obtain the aramid nanofiber solution; Step S12: adding the boron nitride nanosheets into the solvent and performing a first high-speed shear emulsification to achieve effective exfoliation, and performing a second high-speed shear emulsification to mix the effectively exfoliated boron nitride nanosheets and aramid nanofibers to obtain the boron nitride nanosheet-aramid nanofiber mixed solution; Wherein, the solvent is at least one of trifluoromethanesulfonic acid, chlorosulfonic acid or methanesulfonic acid.

3. The preparation method according to claim 2, characterized in that: The shearing speed of the high-speed shear emulsification in step S11 is 6000-20000 rpm, and the shearing time is 2-20 min; The shearing speed of the first high-speed shear emulsification in step S12 is 6000-20000 rpm, and the shearing time is 1-3 hours. The shearing speed of the second high-speed shear emulsification is 6000-20000 rpm, and the shearing time is 2-20 minutes.

4. The preparation method according to claim 3, characterized in that: The thickness of the effectively peeled boron nitride nanosheets is less than 10 nm, and the average sheet diameter is 500 nm to 2 μm.

5. The preparation method according to claim 1, characterized in that: The concentration of the aramid nanofiber solution is 10 to 100 mg / mL; The concentration of the boron nitride nanosheet-aramid nanofiber mixed solution is 20-200 mg / mL.

6. The preparation method according to claim 1, characterized in that: The drying temperature is 60 to 200° C., and the drying time is 10 to 60 minutes.

7. The preparation method according to claim 1, characterized in that: Step S2 specifically includes the following steps: The boron nitride nanosheet-aramid nanofiber mixed solution is connected to the outer channel of the coaxial needle, and the aramid nanofiber solution is connected to the inner channel of the coaxial needle. The fibers are extruded through the coaxial needle, and the extruded fibers are drawn and refined while passing through the coagulation liquid to obtain the gel-state coaxial fiber precursor.

8. The preparation method according to claim 7, characterized in that: The extrusion spinning rate of the inner channel is 0.05 to 0.5 mL / min, and the extrusion spinning rate of the outer channel is 0.1 to 1 mL / min; the extrusion spinning rate ratio of the inner channel to the outer channel is 1:4 to 4:1; The coagulation liquid is at least one of deionized water, ethanol or isopropanol; the line speed of the wire drawing process is 3 to 30 cm / s.

9. A boron nitride-aramid composite coaxial fiber, characterized in that: The boron nitride-aramid composite coaxial fiber is prepared by the preparation method described in any one of claims 1 to 8; the boron nitride-aramid composite coaxial fiber comprises an outer shell layer composed of a boron nitride nanosheet-aramid nanofiber composite material, and a core layer composed of aramid nanofibers.

10. The boron nitride-aramid composite coaxial fiber according to claim 9, characterized in that: The diameter of the boron nitride-aramid composite coaxial fiber is 60-200 μm, the thickness of the outer shell layer is 20-50 μm, and the diameter of the core layer is 20-100 μm; the ratio of the diameter of the boron nitride-aramid composite coaxial fiber to the diameter of the core layer is 3:1-1:3.